Management of climate-related hazards in Germany through adaptive social protection: The case of the Ahr Valley Flooding in 2021 - Jana Martens (Hochschule Bonn-Rhein-Sieg, Fachbereich Sozialpolitik und Soziale Sicherung, 2024)
In July 2021, unprecedented water levels affected Germany, Belgium, and the Netherlands. From July 12 to 15, 2021, a storm complex stalled over the European region, leading to heavy rain and flooding. In Germany, a month's rainfall fell within 48 hours. Soils were heavily saturated after a wet spring, leading to extraordinary water levels. Due to its surrounding landscape, the Ahr river meanders through the steep rocky vineyards. People settled and built in the areas close to the river, which overflowed its banks. More than 130 died. The floodwaters destroyed critical public infrastructure. Buildings collapsed, roads and railways were destroyed, and thousands lost their homes, causing billions of euros in economic loss. The recovery efforts in Germany continue three years after the disastrous event, despite well-developed response procedures and highly established social protection systems. Through the literature review using a qualitative case study approach, the article assesses the floods' impact on the Ahr valley and analyzes climate-related flood hazard management processes in Germany. The theoretical framework focuses on policies and programs reducing communities' vulnerability to climate-related hazards while promoting long-term resilience and sustainable development. Transformative change is possible along four building blocks, namely data and information systems, programs, institutional arrangements, and partnerships, as well as finance. Germany can reduce the disaster risk of climate-related flood hazards by strengthening its control and management capacities as well as enhancing readiness and resilience against future climate-related threats.
urn:nbn:de:hbz:1044-opus-84979
Keywords: 360; Resilience; Germany; Climate; Floods; Risk